Dump the pump: manual aspiration thrombectomy (MAT) with a syringe is technically effective, expeditious, and cost-efficient. (10th November 2017) - Gross, Bradley A; Jadhav, Ashutosh P; Jovin, Tudor G; Jankowitz, Brian Thomas
Abstract : Introduction: Syringe aspiration for manual aspiration thrombectomy (MAT) is a cost- and time-efficient alternative to an aspiration pump with likely similar efficacy. It is counterintuitive to expect the pump to perform better than direct vacuum with a syringe, as the pump must deliver vacuum additionally through a canister and meters of tubing. Objective: To present in vitro and clinical results of MAT with a syringe. Methods: An in vitro analysis was performed comparing vacuum pressures generated by syringe aspiration and with pump aspiration. This was then complemented with prospective clinical data providing details of angiographic and clinical outcomes for syringe MAT. Results: The in vitro analysis demonstrated that equal to slightly greater vacuum pressures were generated by a 60 cc syringe as compared with the pump in both static and partial flow conditions. In our clinical series, 106/113 acute stroke thrombectomies over a 6-month period were performed with syringe MAT on the first pass. Syringe usage instead of pump tubing and a canister led to a total savings of $58 300. The rate of Thrombolysis in Cerebral Infarction 2b/3 recanalization was 93%. Adjunctive stentriever usage was performed in 23% of cases. Median puncture to reperfusion time was 25 min; mean change in National Institute of Health Stroke Scale score at 24 hours was an improvement of 5.1 (median 6). The in-hospital mortality rate was 10%. Seventy percent of patients were discharged to home (modified Rankin Scale (mRS) score 0–2) or a rehabilitation facility (mRS score 2–4). Conclusion: MAT using a syringe is a safe, fast, and more cost-effective approach than using an aspiration pump.